Strategies to Target ISG15 and USP18 Toward Therapeutic Applications - Jiménez Fernández, Daniel; Hess, Sandra; Knobeloch, Klaus-Peter (Frontiers in Chemistry, 2020)
The interferon (IFN)-stimulated gene product 15 (ISG15) represents an ubiquitin-like protein (Ubl) which in a process termed ISGylation can be covalently linked to target substrates via a cascade of E1, E2 and E3 enzymes. Furthermore, ISG15 exerts functions in its free form both, as an intracellular and as a secreted protein. In agreement with its role as a type I IFN effector, most functions of ISG15 and ISGylation are linked to the anti-pathogenic response. However, also key roles in other cellular processes such as protein translation, cytoskeleton dynamics, exosome secretion, autophagy or genome stability and cancer were described. Ubiquitin-specific protease 18 (USP18) constitutes the major ISG15 specific protease which counteracts ISG15 conjugation. Remarkably, USP18 also functions as a critical negative regulator of the IFN response irrespective of its enzymatic activity. Concordantly, lack of USP18 function causes fatal interferonopathies in humans and mice. The negative regulatory function of USP18 in IFN signaling is regulated by various protein-protein interactions and its stability is controlled via proteasomal degradation. The broad repertoire of physiological functions and regulation of ISG15 and USP18 offers a variety of potential intervention strategies which might be of therapeutic use. Due to the high mutation rates of pathogens which are often species specific and constantly give rise to a variety of immune evasion mechanisms, immune effector systems are under constant evolutionarily pressure. Therefore, it is not surprising that considerable differences in ISG15 with respect to function and sequence exist even among closely related species. Hence, it is essential to thoroughly evaluate the translational potential of results obtained in model organisms especially for therapeutic strategies. This review covers existing and conceptual assay systems to target and identify modulators of ISG15, ISGylation, USP18 function and protein-protein interactions within this context. Strategies comprise mouse models for translational perspectives, cell-based and biochemical assays as well as chemical probes.